2022
DOI: 10.3390/v14071435
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Humoral Immune Response against the Type 2 Porcine Reproductive and Respiratory Syndrome Virus via Different Immune Pathways

Abstract: The intramuscular vaccine is the principal strategy to protect pigs from porcine reproductive and respiratory syndrome virus (PRRSV), However, it is still difficult to control PRRSV effectively. This study infected piglets with PRRSV through intramuscular and intranasal inoculation. Subsequently, viral loads, anti-PRRSV antibody levels, and neutralizing antibodies (NAs) titers in both serum and saliva were monitored for 43 days. Meanwhile, tissues were obtained through necropsy at 43 days post-inoculation (dpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The PRRSV HeN-3 strain (GenBank ID: ON645930, PRRSV-2) used in this study has been described previously [ 22 ]. The PCV2b, which was a kind gift from Qianyue Jin (Henan Academy of Agricultural Sciences, Zhengzhou, China), was used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The PRRSV HeN-3 strain (GenBank ID: ON645930, PRRSV-2) used in this study has been described previously [ 22 ]. The PCV2b, which was a kind gift from Qianyue Jin (Henan Academy of Agricultural Sciences, Zhengzhou, China), was used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…PRRSV could evade host innate immunity, leading to a delayed response of NAs and immunosuppression [ 8 , 12 , 22 ]. PRRSV structural protein GP5 has a neutralizing epitope and plays an important role in the pathogenicity and immune evasion of PRRSV [ 16 , 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although vaccination is the most effective method to prevent PRRSV infection, the efficacy of PRRSV vaccines remains unsatisfactory [ 9 , 10 , 11 ]. It is reported that neutralizing antibodies (NAs) play a significant role in protecting pigs against PRRSV infection, but the delayed response of NAs leads to the low effectiveness of PRRSV vaccines [ 12 , 13 ]. Thus, it is essential to explore the biological processes and the molecular mechanisms underlying PRRSV infection.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that intranasal vaccination can improve the local response against respiratory pathogens ( 34 , 35 ). The immune response we obtained with nasal immunization is characterized by the production of IgG and IgA immunoglobulins in serum and IgM and IgA in mucosa (measured in bronchoalveolar lavage fluid).…”
Section: Discussionmentioning
confidence: 99%